2008
DOI: 10.1159/000150099
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Persistence of Cardiovascular and Locomotor Effects of Immobilization Stress and Influence of ACTH Treatment

Abstract: (13 IU/kg, s.c.) triggered a short-lived rise in MAP, and decreased HR. After six daily injections of ACTH and recovery time (8 days), rats were immobilized as above. The cardiovascular responses were similar during the IMO, but the ACTHpretreated group displayed differences following cessation of the IMO. In addition, IMO led to a large reduction of locomotor activity during the dark (normally active) phase to levels similar to the light phase. Following the IMOs, locomotor activity recovered more slowly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 96 publications
1
18
0
Order By: Relevance
“…9) Along with other biological responses, stressors activate the hypothalamic-pituitaryadrenal (HPA) axis and increase the release of monoamines into the hippocampus, hypothalamus, and striatum, which are brain regions that have been associated with anxiety and depression. 10) Notwithstanding adaptive neurochemical changes, sufficient intensity and persistence of stressors may place excessive strain on these biological processes, leading to allostatic overload and the development of psychological and physical disorders.…”
Section: )mentioning
confidence: 99%
“…9) Along with other biological responses, stressors activate the hypothalamic-pituitaryadrenal (HPA) axis and increase the release of monoamines into the hippocampus, hypothalamus, and striatum, which are brain regions that have been associated with anxiety and depression. 10) Notwithstanding adaptive neurochemical changes, sufficient intensity and persistence of stressors may place excessive strain on these biological processes, leading to allostatic overload and the development of psychological and physical disorders.…”
Section: )mentioning
confidence: 99%
“…To evaluate the general validity of previous results, we employed another type of stressor—restraint. Based on previous studies 16,28 , we hypothesized that prolonged stress would produce a significantly greater effect on heart biorhythm parameters than acute stress. In previous reports, it has been shown that repeated stress has more pronounced effects on different parameters (haemodynamic, heart, vascular) in experimental animals than acute stress effects.…”
Section: Introductionmentioning
confidence: 99%
“…One study found when rats were immobilized two hours a day for six days their in-cage overnight locomotor activity decreased significantly [Sabban et al, 2009]. This study found exposure to even one session of immobilization led to significant decreases in locomotor activity overnight [Sabban et al, 2009].…”
mentioning
confidence: 75%
“…One study found when rats were immobilized two hours a day for six days their in-cage overnight locomotor activity decreased significantly [Sabban et al, 2009]. This study found exposure to even one session of immobilization led to significant decreases in locomotor activity overnight [Sabban et al, 2009]. Furthermore, another study found chronic mild stress resulted in reduced spontaneous locomotor activity throughout the duration of exposure when presented for four weeks [Grippo et al, 2003].…”
mentioning
confidence: 91%
See 1 more Smart Citation